Survival Strategies For Farmer Workers In Bandar Tongging Village, Merek District, Karo Regency - Sebayang, Rebekha Prisilia; Putra Kasea Sinaga, Randa (Journal of Peasants' Rights, 2022)
There are various ways that individuals or groups do to be able to meet their needs. These methods are known as survival strategies. Farm workers in Bandar Tongging Village, Merek District, Karo Regency are a group of people who have a low economy. Efforts made by farmers to meet basic needs by strengthening their business by taking advantage of existing opportunities, despite their weaknesses or limitations. Basic needs in the form of food, clothing, housing, health, and education needs. This study aims to find out about the strategies used by farm workers so that they can survive. Data collection techniques were carried out by literature study, observation, interviews, and documentation. The data obtained in the field are then analyzed qualitatively to obtain conclusions. The results of this study also show how the family of farm workers in the strategy carried out to meet basic needs by using an active strategy, namely by looking for additional income by doing side jobs, and employing family members who are of working age. The passive strategy is to save on the food menu they consume daily, stop giving their children formula milk, not buy new clothes, and even send their children to public schools.